Going Through The Roof: On Prices for Drugs Sold Through Insurance - Jurjen Kamphorst; Vladimir Karamychev (Tinbergen Institute, 2021)
We offer a theory of how the combination of budget constraints and insurance drives up prices. A natural context for our theory is the health care market, where drug prices can be very high. Our model predicts that monopoly prices for orphan drugs are inversely related to the prevalence up until a maximum price. This is supported by empirical evidence in the literature. As a result, prices of drugs sold by a monopoly treating rare serious diseases are doomed to go sky high.
Keywords: D42; G22; I13; 330; Monopoly pricing; Insurance; Orphan Drugs